THE EFFECT OF THE USE OF PAPAIN ENZYM ON LIMELAYER REMOVING FROM THE SKIN OF SEA CUCUMBER(Holothuria scabra) - Dimas Prasetia; Mery Sukmiwati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was aimed to observe the using of papain enzyme to remove the limelayer from the skin of sea cucumber (Holothuria scabra) by applying boiling method. The research was using an experimental method and composing as nonfactorial randomized completely design. The treatment conducted was the using of papain enzymes at different concentrations(0, 0.05, 0.1, and 0.15 %) and boiled at the temperature of 60oC. The parameters used were sensory evaluation, included the value of texture and aroma, the content of calcium, and the proximate composition. The results showed that the use of the papain enzyme wasaffecting to the removal of lime layer from the skin of the sea cucumber, indicated by the significantly different of the appearance and the texturevalue, and the calciumcontent, but not affecting to the aroma value. The proximate composition showed that the content of water 83.32% wb, ash 20.26% db, fat 10.76% db, carbohydrate (by difference) 7.10% db, and protein 80.06% db. Keywords: Papain enzyme, limestone layer, and sea cucumber